Primary Immunodeficiency Diseases: Current and Emerging Therapeutics - Marciano, Beatriz E.; Holland, Steven M. (Frontiers in Immunology, 2017)
Primary immunodeficiency diseases (PID) result from defects in genes affecting the immune and other systems in many and varied ways (1, 2). Until the last few years, treatments have been largely supportive, with the exception of bone marrow transplantation. However, recent advances in immunobiology, genetics, and the explosion of discovery and commercialization of biologic modifiers have drastically altered the landscape and opportunities in clinical immunology. Therapeutic options and life expectancy of PID patients have also improved dramatically, in large part as a result of better prevention and treatment of infections as well as better understanding and treatment of autoimmune complications (3). As early-life infection-related mortality declines we should anticipate the emergence of other conditions that were previously not appreciated, including malignancies and degenerative disorders unmasked by increasing longevity (4). The genomic revolution has identified literally hundreds of new genetic etiologies of immune dysfunction, many of which are or will soon be eligible for targeted therapies. These emerging immunomodulatory agents represent new therapeutic options in PIDs (5).